The Inflow of Foreign Direct Investments into the Kingdom of Saudi Arabia - Alharbi, Jaithen Abdullah (2009)
This study generally concentrates on the foreign direct investment by the multinational companies in Saudi Arabia. Also, this study contributes to understand more about the foreign direct investment in the developing countries particularly in Saudi Arabia and the role of the government to attract the foreign direct investment to the country. It also analyze motives and drivers of the FDI inflow into Saudi Arabia.